Increasing of malignant pleural mesothelioma : burning issue in Split-Dalmatian County, Croatia - Miše, Kornelija; Jurčev Savičević, Anamarija; Bradarić, Anteo; Perić, Irena; Barišić, Igor, liječnik; Puntarić, Dinko; Miše, Joško; Ilić, Nenad, liječnik (2009)
Abstract: Asbestos-related diseases are one of the burning public health issues worldwide. The incidence and the epidemiological patterns of malignant pleural mesothelioma in Split-Dalmatian County, where a large part of Croatian industry related to asbestos processing and use have been situated were assessed in this study. The history of asbestos-related issues and development of current legislation in Croatia was also discussed briefly. Data on the incidence were collected retrospectively from the medical records of patients with malignant pleural mesothelioma treated at Department of Pulmonary Diseases University Hospital Split during the 2000–2007 period. A total of 137 new cases was recorded with the mean incidence of 3.55/100 000 and the trend was increasing over years compared with 1992–1995 period in the same county when the mean incidence was 1.7/100000. Men accounted for 85.4% of all cases. The mean age of patients was 64.9±15.4 years. The majority of patients were occupationally exposed to asbestos (85.4%), 8.8% had environmental exposure, and 2.2% had domestic exposure. The type of household exposition was in 5.8% of patients. More than half of the cases were exposed to asbestos 31–40 years. The mean length of exposure was 28.87±15.63 years. The incidence of malignant pleural mesothelioma in Split-Dalmatian County has been obviously increasing due to the predominantly occupational exposure and it is reasonable to assume that it will remain high in the next two –three decades and to be a reason for concern and fear among the general population
Bibliografija: 26 jed
Sažetak
Keywords: Maligni mezoteliom pleure; Splitsko-dalmatinska županija